A novel tension strap connection for rapid assembly of temporary timber structures. (1st July 2022) - Xin, Zhuo-Yang; Baber, Kim; Gattas, Joseph M.
Abstract: Emergency temporary housing is a critical component of post-disaster response and recovery. Their successful deployment requires structures to be low cost, easy to assemble, and with a capacity to adapt to local material and manufacturing availability. This paper proposes a novel 'strap joint' for the rapid assembly of lightweight timber elements and prefabricated panels. The joint utilises a low-cost and widely available packaging strap material, tensioned around timber elements to form a semi-rigid, adaptable structural connection. Experimental, numerical, and theoretical studies were conducted to evaluate joint semi-rigid structural behaviour. Joints are observed to possess a non-linear and highly ductile moment–rotation response, that arises from tension strap elongation, timber local bearing, and joint rotational deformation. A portal frame numerical model and full-scale physical prototype are also developed to contextualise the utility of the proposed strap connection for an emergency housing application. Highlights: A novel semi-rigid connection is proposed utilising post-tensioned packaging strap material. The 'strap' connection enables rapid and low-cost assembly of lightweight timber elements. Joints behave with a non-linear and highly ductile rotational response. The structural behaviour of an emergency house is simulated using joint rotational stiffness values.